Assessing The In Vitro Efficacy Of Agrochemicals And Antagonist Against Major Seed Borne Fungi Of Pearl Millet (Journal of Plant Disease Sciences, 2023)
The significant millet crop grown in India is pearl millet, which has a slightly superior amino acid profile and is high in protein. Using blotter paper, four seed-borne fungus were isolated: Alternaria alternata, Curvularia penniseti, Bipolaris setariae, and Fusarium moniliforme. The fungicides and antagonists were then assessed using the poisoned food and dual culture techniques, respectively. Tebuconazole (0.1%), Copper oxychloride (0.25%) were found most effective fungicides over all other treatments for arresting the mycelial growth (100%) of all associated seed borne fungi followed by combi product Carbendazim + Mancozeb (0.25%). The most efficient fungal bioagent against seed-borne fungus among the antagonists was Trichoderma asperellum, followed by Trichoderma harzianum. In comparison to fungal antagonists, bacterial antagonists Bacillus subtilis and Pseudomonas fluorescence were shown to be less potent.
Keywords: Bioagents; Fungicides; Mycoflora; Pearl millet; Seeds